(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the role and importance of electronic didactic support in developing the methodological readiness of future primary school teachers. It highlights the content of educational and methodological materials created on the basis of modern information and communication technologies, their role in shaping teachers professionally, and ways to implement them in practice. The article also discusses the interactivity of electronic didactic tools, opportunities for independent learning, and aspects that serve to increase educational effectiveness. Based on research findings, recommendations highlight prospects for improving electronic learning resources.